1967
DOI: 10.3133/pp524h
|View full text |Cite
|
Sign up to set email alerts
|

Ash flows and related volcanic rocks associated with the Creede Caldera, San Juan Mountains, Colorado

Abstract: Other properties____________________________ 12 Evidence of flow boundaries _____________________ _ Chemical composition and alteration______________ 13 West Bellows Creek section _______-_____-___ _ Depositional and modifying processes_______ _ _ _ _ _ _ _ 14 East Bellows Creek section __________________ _ Origin of eutaxitic and fluidal structures_______

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 7 publications
3
69
0
Order By: Relevance
“…In our case, some samples are typically high in K 2 O and low in Na 2 O because of alkali exchange (e.g., Lipman 1964); this behavior, reflecting a reasonable potassium metasomatism (e.g., Ratté and Steven 1967;Sweetkind et al 1993), may be related to preweathering K enrichment within source terranes (e.g., Fedo et al 1995). As a consequence, the CIA should correctly detect the degree of weathering in source areas.…”
Section: Paleoweathering Sorting and Recycling Processesmentioning
confidence: 99%
“…In our case, some samples are typically high in K 2 O and low in Na 2 O because of alkali exchange (e.g., Lipman 1964); this behavior, reflecting a reasonable potassium metasomatism (e.g., Ratté and Steven 1967;Sweetkind et al 1993), may be related to preweathering K enrichment within source terranes (e.g., Fedo et al 1995). As a consequence, the CIA should correctly detect the degree of weathering in source areas.…”
Section: Paleoweathering Sorting and Recycling Processesmentioning
confidence: 99%
“…Clearly, Lake Creede was influenced by a complex interplay among the tectonic and volcanic history of the region and local climatic, geochemical and hydrological conditions (Finkelstein et al 1999, Larsen & Smith 1999. Wolfe & Schorn (1989) accepted a radiometric date of 27.2 (Ratte & Steven 1967; correction made for recent decay constants), placing the formation in the late Oligocene.…”
Section: Late Eoceneearly Oligocene In the Rocky Mountainsmentioning
confidence: 99%
“…Samples usually are described as partly welded, moderately welded, or densely welded. Because of the direct relationship between porosity and the degree of welding, Ratte and Steven (1967) suggested that a numerical value of porosity would more effectively express the degree of welding than the undefined terms listed above. They would classify rocks having less than 10 percent porosity as densely welded and those having more than 10 percent as partly welded.…”
Section: Characteristics Of Surface Exposuresmentioning
confidence: 99%